How English Foreign Language Students’ Autonomy and Digital Competence Relate to Their Writing Achievement - Andina, Diah Maya; Cahyono, Bambang Yudi; Widiati, Utami (Tadris: Jurnal Keguruan dan Ilmu Tarbiyah, 2020)
This study aimed to examine the correlation between learner autonomy, digital competence, and writing achievement. It involved 92 first-year English as a Foreign Language (EFL) students who were enrolled in an intensive course (IC) program of the English department of a state university in Indonesia. This study used three types of data: learner autonomy level elicited by using a questionnaire, digital competence level elicited by using a questionnaire, writing scores that were obtained from the coordinator of the IC program. The research methodology used in this study was quantitative research. The bivariate Spearman correlation was applied to know the correlations between learner autonomy and writing achievement and the correlation between digital competence and writing achievement. The multiple linear regression was computed to examine the correlation of the combination of learner autonomy and digital competence towards writing achievement. The results of the study confirmed that learner autonomy was strongly correlated with writing achievement and digital competence was moderately correlated with writing achievement. The result also showed that there is a statistically significant correlation between a combination of learner autonomy and digital competence towards writing achievement. Therefore, pedagogically, teachers of EFL writing are suggested to promote autonomous learning and at the same time, use technology to foster EFL students' writing achievement.